Acute encephalopathy with parvovirus B19 infection in sickle cell disease. Issue 6 (1st December 2002) - Bakhshi, S; Sarnaik, S A; Becker, C; Shurney, W W; Nigro, M; Savaşan, S
Abstract : A 13 year old girl with haemoglobin Sβ + thalassaemia developed simultaneous aplastic crisis and encephalopathy associated with parvovirus B19 (PB19) infection. Brain magnetic resonance imaging findings were consistent with central nervous system (CNS) vasculitis and her symptoms resolved with steroid therapy. Thus, PB19 induced CNS hypersensitivity vasculitis must be considered in the differential diagnosis of encephalopathy.